The Museum Of Anthropology And Ethnography Saint Petersburg And The Temporalization Of The Russian Empire - Hügel, Johanna (Lidé města, 2024)
Focusing on imperial depictions of the Amur region, this article examines the Museum of Anthropology and Ethnography, Saint Petersburg (MAE) as a central agent in the production and institutionalization of images of empire. Within the walls of this museum, the imperial elites of Saint Petersburg-based geographers, ethnographers, curators, and museum visitors imagined and constructed the only recently conquered far-eastern portion of the Russian Empire as not only a spatially, but also temporally remote place. Carefully arranged according to the logic of evolutionary anthropology, the exhibition resonated well with the interests of the avant-garde artist and art critic Vladimir Markov, who searched for “primitive art” and visited the collection in 1913. Influenced by the most recent publications of his contemporaries on the interconnections between aesthetics and psychology, Markov found that the objects perfectly embodied the pureness and timelessness he was looking for.